Proses Komunikasi Dalam Pemberdayaan Kelompok Perempuan Penenun Di Desa Poto Kecamatan Moyo Hilir (Studi Komunikasi Menggunakan Teori SMCR) - Erma Ade Lestari; Fahrunnisa Fahrunnisa (Al Makki Publisher, 2023)
The empowerment of women weavers has an important role in local economic development and cultural preservation. The weaver group in Poto Village is one of the women's groups that participated in empowerment activities with assistance from the Department of Industry and Trade. The existence of this empowerment process is supported by a good and effective communication process so that it is expected to maximize the potential of women weavers in Poto Village. Thus, this study aims to determine the effective communication process in the process of empowering weavers in Poto Village. The effective communication approach used in this study is the SMCR model initiated by David K. Berlo with elements of effective communication which include source, message, channel and receiver. This research is qualitatively descriptive. Research informants were taken using purposive sampling techniques, obtained 7 informants, namely the Head of Poto Village, representatives of Disperindag, and 5 weavers of Poto Village. From the interview results, factors of communication skills, attitudes, knowledge, and socio-cultural position from the source party (village government and Disperindag) and receiver (weaver group) affect the success of communication. Disperindag and village cooperation provides training, mentoring, and budget allocation. The empowerment material is clearly understood by the weaver. Communication media such as WhatsApp, Zoom, and in-person meetings help in the delivery of messages.